2015
DOI: 10.1021/cn500202c
|View full text |Cite
|
Sign up to set email alerts
|

Single-Quantum-Dot Tracking Reveals Altered Membrane Dynamics of an Attention-Deficit/Hyperactivity-Disorder-Derived Dopamine Transporter Coding Variant

Abstract: The presynaptic, cocaine- and amphetamine-sensitive dopamine (DA) transporter (DAT, SLC6A3) controls the intensity and duration of synaptic dopamine signals by rapid clearance of DA back into presynaptic nerve terminals. Abnormalities in DAT-mediated DA clearance have been linked to a variety of neuropsychiatric disorders, including addiction, autism, and attention deficit/hyperactivity disorder (ADHD). Membrane trafficking of DAT appears to be an important, albeit incompletely understood, post-translational r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 62 publications
1
55
0
Order By: Relevance
“…However, it is unclear whether antibody-bound DAT traffics similar to native DAT, as we investigate here. Multiple studies also demonstrate that DAT partitions into cholesterol-rich membrane microdomains (36,(39)(40)(41)(42)(43)(44) and that the membrane raft protein flotillin-1 is required for PKC-and AMPH-mediated DAT internalization (42), consistent with a clathrin-independent endocytic mechanism. However, a separate study reported that flotillin-1 contributes to DAT membrane mobility rather than PKC-stimulated DAT internalization (45).…”
Section: Discussionmentioning
confidence: 92%
“…However, it is unclear whether antibody-bound DAT traffics similar to native DAT, as we investigate here. Multiple studies also demonstrate that DAT partitions into cholesterol-rich membrane microdomains (36,(39)(40)(41)(42)(43)(44) and that the membrane raft protein flotillin-1 is required for PKC-and AMPH-mediated DAT internalization (42), consistent with a clathrin-independent endocytic mechanism. However, a separate study reported that flotillin-1 contributes to DAT membrane mobility rather than PKC-stimulated DAT internalization (45).…”
Section: Discussionmentioning
confidence: 92%
“…Importantly, A559V knock in mice were recently found to display both behavioral and functional alteration, supporting a significant impact of ADE in vivo (66). It is therefore also highly interesting that the R615C variant, has been found to undergo dysregulated trafficking with enhanced constitutive internalization and altered microdomain distribution (28,67). This finding further supports that the potential pathological impact of altered DAT function is not necessarily recapitulated in direct assessment of dopamine uptake, and that there might be facets of DAT function that require a native context to uncover.…”
Section: Discussionmentioning
confidence: 96%
“…The authors postulated that there is increased PKC signaling due to D2R activation in the mutant causing the redistribution and trafficking perturbation (Bowton et al, 2014). Additionally, using a novel experimental approach that employed quantum dot labeling of DAT, Kovtun et al showed that neuropsychiatric-associated variants in DAT caused an increase in membrane diffusion and constitutive endocytosis and recycling (Kovtun et al, 2015). These studies linking DAT to ASDs show how disturbances in its function and its membrane trafficking have the ability to directly affect neurological phenotypes, but they also intimately connect its surface trafficking to its function.…”
Section: : Reviewmentioning
confidence: 99%